2007
DOI: 10.1152/ajpregu.00244.2007
|View full text |Cite
|
Sign up to set email alerts
|

GSK-3β activity is increased in skeletal muscle after burn injury in rats

Abstract: Previous reports suggest that burn-induced muscle proteolysis can be inhibited by treatment with GSK-3beta inhibitors, suggesting that burn injury may be associated with increased GSK-3beta activity. The influence of burn injury on muscle GSK-3beta activity, however, is not known. We determined the effect of a 30% total body surface full-thickness burn injury in rats on muscle GSK-3beta activity by measuring GSK-3beta activity and tissue levels of serine 9 phosphorylated GSK-3beta, p(Ser9)-GSK-3beta, by Wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…For example, inhibition of Akt activity results in reduced phosphorylation (activation) of GSK-3␤. Recent observations support a role of activated GSK-3␤ in muscle wasting caused by sepsis (31) and burn injury (32). Thus, in a recent study (31) we found that muscle levels of phosphorylated (Ser9) GSK-3␤ were reduced in muscles from septic rats, consistent with activation of the kinase, and in the same study, treatment of septic muscles with GSK-3␤ inhibitors reduced protein breakdown.…”
Section: Calpain Activation Downregulates Akt Activity In Skeletal Musupporting
confidence: 77%
See 1 more Smart Citation
“…For example, inhibition of Akt activity results in reduced phosphorylation (activation) of GSK-3␤. Recent observations support a role of activated GSK-3␤ in muscle wasting caused by sepsis (31) and burn injury (32). Thus, in a recent study (31) we found that muscle levels of phosphorylated (Ser9) GSK-3␤ were reduced in muscles from septic rats, consistent with activation of the kinase, and in the same study, treatment of septic muscles with GSK-3␤ inhibitors reduced protein breakdown.…”
Section: Calpain Activation Downregulates Akt Activity In Skeletal Musupporting
confidence: 77%
“…Thus, in a recent study (31) we found that muscle levels of phosphorylated (Ser9) GSK-3␤ were reduced in muscles from septic rats, consistent with activation of the kinase, and in the same study, treatment of septic muscles with GSK-3␤ inhibitors reduced protein breakdown. In another study (32), burn-induced muscle proteolysis was associated with activation of GSK-3␤ determined as reduced p(Ser9)-GSK-3␤ levels and increased GSK-3␤ kinase activity. Reduced phosphorylation and activity of mTOR, downstream of inhibited Akt activity, are important for the development of muscle wasting mainly by inhibition of protein synthesis (61).…”
Section: Calpain Activation Downregulates Akt Activity In Skeletal Mumentioning
confidence: 95%
“…Studies in skeletal muscles have linked GSK-3b to muscle-wasting conditions. GSK-3b activity has been shown to increase in aged (Kinnard et al, 2005) and burn-injured skeletal muscles (Fang et al, 2007). Inhibition of GSK-3b is required for IGF-1-induced myogenic differentiation (Vyas et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The activation of Akt signal has an antiapoptotic/ survival and cytoprotective functions in skeletal muscle cells (Conejo and Lorenzo 2001;Lawlor and Rotwein 2000). It has been also reported that the inhibition of GSK3 , which is induced by the phosphorylation, facilitates the diVerentiation of muscle cells (Fang et al 2005;Fang et al 2007;van der Velden et al 2006;van der Velden et al 2007;Vyas et al 2002). Recently, it was reported that the administration of G-CSF could reduce apoptosis in injured skeletal muscle (Stratos et al 2007).…”
Section: Discussionmentioning
confidence: 99%